2012
DOI: 10.3390/ma5071176
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Actin Filament Quantification of Osteoblasts and Their Morphometric Analysis on Microtextured Silicon-Titanium Arrays

Abstract: Microtexturing of implant surfaces is of major relevance in the endeavor to improve biorelevant implant designs. In order to elucidate the role of biomaterial’s topography on cell physiology, obtaining quantitative correlations between cellular behavior and distinct microarchitectural properties is in great demand. Until now, the microscopically observed reorganization of the cytoskeleton on structured biomaterials has been difficult to convert into data. We used geometrically microtextured silicon-titanium ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…Taking the unaltered level of the number and length of actin filaments for Ti and TiPPAAm into account, these results indicate that the enhancement of cell area elicited by PPAAm is carried out by cells without a distinct increase in the number or length of actin filaments. This assumption can be affirmed by in vitro data from (Matschegewski et al, 2010). Herein, the authors describe the behaviour of MG-63 osteoblasts on defined micropillar-structured surfaces, where cell orientation and spreading occurred despite the complete lack of organised actin fibres, but cells showed short filamentous actin solely on top of the pillars similar to what we see in the presence of CD.…”
Section: F Kunz Et Alsupporting
confidence: 61%
See 1 more Smart Citation
“…Taking the unaltered level of the number and length of actin filaments for Ti and TiPPAAm into account, these results indicate that the enhancement of cell area elicited by PPAAm is carried out by cells without a distinct increase in the number or length of actin filaments. This assumption can be affirmed by in vitro data from (Matschegewski et al, 2010). Herein, the authors describe the behaviour of MG-63 osteoblasts on defined micropillar-structured surfaces, where cell orientation and spreading occurred despite the complete lack of organised actin fibres, but cells showed short filamentous actin solely on top of the pillars similar to what we see in the presence of CD.…”
Section: F Kunz Et Alsupporting
confidence: 61%
“…The microscopic images were processed in three steps according to (Matschegewski et al, 2012): pre-processing, feature detection and quantification. Before feature detection, the main sources of errors were reduced, namely noise, by variational methods (Birkholz, 2011b) , 2008).…”
Section: Quantification Of Actin Filaments Using Mathematical Image Pmentioning
confidence: 99%
“…For example the lateral spacing of the nanotube system was varied by altering the tube diameter between 30 and 100 nm. On such topographies, cells alter not only the phenotype but also their internal architecture, e.g., the actin cytoskeleton, in a surface geometrydependent manner [14,15] (Figure 1).…”
Section: Cell Regulation By Physical Characteristics Of a Materials Tomentioning
confidence: 99%
“…16,20,21 Micropits and micropillars are typically arranged in an organized manner (isotropic) rather than an unorganized manner (anisotropic) on the microgrooves. 22 It has been reported that the microscopic bone properties of cancellous and cortical bone enable them to be more suitable for use with the anisotropic surface for interlocking. 23 Nanoleaves may provide a larger contact area for adherent cells compared to nanoplates; however, the production process is complicated.…”
Section: Introductionmentioning
confidence: 99%